Grammar rules! - Gibb, Tanya (Claremont Macmillan Education, 2015)
"'Grammar Rules!' is a whole-school grammar program built on a context-based approach to teaching and learning. The series covers grammatical structures for particular text types, purposes and audiences. Your students will learn about grammar from the contextual level of the whole text down to the sentence and word level. They'll also learn how to use that grammar knowledge when responding to texts and when constructing their own texts. Full teacher support for the 'Grammar Rules!' program is provided by the teacher resource books. These books can be used alongside the six student books, or to support your own whole-school program. In each teacher resource book you'll find: valuable background information about teaching grammar; strategies and activities for teaching grammar; annotated text type models; strategies for assessing grammar; student work samples; teaching notes for every unit in the student books; all answers for the student books."--Back cover, teacher resource books
Include Illustrations
Keywords: English Language Grammar Study and Teaching (Primary)